2023
DOI: 10.1111/acel.14067
|View full text |Cite
|
Sign up to set email alerts
|

Optimum ratio of dietary protein and carbohydrate that maximises lifespan is shared among related insect species

Juliano Morimoto

Abstract: Animals often regulate the intake and quantity of nutrients to maximise fitness through life‐history traits such as lifespan, but we still lack a proper understanding of how specific nutrients influence these traits. Here, I developed an algorithm which allowed me to create a nutrient‐specific database from literature data, and investigated how the requirements of protein (P) and carbohydrate (C) needed to maximise lifespan evolved across nine insect species. I found moderate evidence of a phylogenetic signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“… 29 , 34 37 , 71 ). In fact, a recent comparative nutrition study showed that lifespan is maximized at lower protein-to-carbohydrate ratios, and that Dipterans often survive the longest in sugar-rich diets ( 72 ). It is important to note that, because there are no holidic diet developed for houseflies in the literature, we cannot interpret our results in relation to protein and carbohydrate ratios alone since our manipulation of protein source also varied other micronutrients which might be important for survival.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 34 37 , 71 ). In fact, a recent comparative nutrition study showed that lifespan is maximized at lower protein-to-carbohydrate ratios, and that Dipterans often survive the longest in sugar-rich diets ( 72 ). It is important to note that, because there are no holidic diet developed for houseflies in the literature, we cannot interpret our results in relation to protein and carbohydrate ratios alone since our manipulation of protein source also varied other micronutrients which might be important for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers utilizing the Geometric Framework for Nutrition (GFN) model have demonstrated that an optimal ratio of protein to carbohydrates enables insects to achieve superior growth, development, and reproductive performance. High protein and low carbohydrate diets, or conversely, low protein and high carbohydrate diets, adversely affect the growth, development, and reproduction of insects [49][50][51][52]. For example, Lee (2008) [51] and Fanson (2009) [53] found that when Drosophila melanogaster and Bactrocera tryoni were fed diets with a lower protein-to-carbohydrate ratio (p:c = 1:16), they exhibited the longest adult lifespans but the lowest fecundity.…”
Section: Effects Of Host Plant Nutritional Differences On the Perform...mentioning
confidence: 99%

Turmeric shortens lifespan in houseflies

Laurie,
Ainslie,
Mitchell
et al. 2024
Preprint
Self Cite